The Unapologetic Mathematician

Mathematics for the interested outsider

Change of Variables for Tensor Fields

We’ve seen that given a local coordinate patch (U,x) we can decompose tensor fields in terms of the coordinate bases \frac{\partial}{\partial x^i} and dx^i on \mathcal{T}_pM and \mathcal{T}^*_pM, respectively. But what happens if we want to pass from the x-coordinate system to another coordinate system y?

For vectors and covectors, we know the answers. We pass from the x-coordinate basis to the y-coordinate basis of \mathcal{T}_pM by using a Jacobian:

\displaystyle\frac{\partial}{\partial x^i}=\sum\limits_{j=1}^n\frac{\partial y^j}{\partial x^i}\frac{\partial}{\partial y^j}

where we calculate the coefficients by writing the coordinate function y^j in terms of the x coordinates. That is, we’re calculating the Jacobian of the function y\circ x^{-1}:\mathbb{R}^n\to\mathbb{R}^n.

Similarly, we pass from the x-coordinate basis to the y-coordinate basis of \mathcal{T}^*_pM by using another Jacobian:

\displaystyle dx^i=\sum\limits_{j=1}^n\frac{\partial x^i}{\partial y^j}dy^j

Where here we use the Jacobian of the inverse transformation x\circ y^{-1}:\mathbb{R}^n\to\mathbb{R}^n.

Since we build up the coordinates on the tensor bundles as the canonical ones induced on the tensor spaces by the coordinate bases on \mathcal{T}_pM and \mathcal{T}^*_pM, we immediately get coordinate transforms for all these bundles.

As one example in particular, given the basis \{dx^i\} and the basis \{dy^j\} on the coordinate patch (U,x) we can build up two “top forms” in \Lambda^*_n(U) — top, since n is the highest possible degree of a differential form. These are dx^1\wedge\dots\wedge dx^n and dy^1\wedge\dots\wedge dy^n, and it turns out there’s a nice formula relating them. We just work it out from the formula above:

\displaystyle\begin{aligned}dx^1\wedge\dots\wedge dx^n&=\left(\sum\limits_{j_1=1}^n\frac{\partial x^1}{\partial y^{j_1}}dy^{j_1}\right)\wedge\dots\wedge\left(\sum\limits_{j_n=1}^n\frac{\partial x^n}{\partial y^{j_n}}dy^{j_n}\right)\\&=\sum\limits_{j_1,\dots,j_n=1}^n\frac{\partial x^1}{\partial y^{j_1}}\dots\frac{\partial x^n}{\partial y^{j_n}}dy^{j_1}\wedge\dots\wedge dy^{j_n}\\&=\sum\limits_{\pi\in S_n}\prod\limits_{i=1}^n\frac{\partial x^i}{\partial y^{\pi(i)}}dy^{\pi(1)}\wedge\dots\wedge dy^{\pi(n)}\\&=\left(\sum\limits_{\pi\in S_n}\prod\limits_{i=1}^n\frac{\partial x^i}{\partial y^{\pi(i)}}\mathrm{sgn}(\pi)\right)dy^1\wedge\dots\wedge dy^n\\&=\det\left(\frac{\partial x^i}{\partial y^j}\right)dy^1\wedge\dots\wedge dy^n\end{aligned}

That is, the two forms differ at each point by a factor of the Jacobian determinant at that point. This is the differential topology version of the change of basis formula for top forms in exterior algebras.

July 8, 2011 - Posted by | Differential Topology, Topology

No comments yet.

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out / Change )

Twitter picture

You are commenting using your Twitter account. Log Out / Change )

Facebook photo

You are commenting using your Facebook account. Log Out / Change )

Google+ photo

You are commenting using your Google+ account. Log Out / Change )

Connecting to %s

Follow

Get every new post delivered to your Inbox.

Join 419 other followers

%d bloggers like this: